2015
DOI: 10.4236/jamp.2015.36078
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of MHD Boundary Layer Flow of Non-Newtonian Casson Fluid on a Moving Wedge with Heat and Mass Transfer and Induced Magnetic Field

Abstract: The paper investigates the numerical solution of the magnetohydrodynamics (MHD) boundary layer flow of non-Newtonian Casson fluid on a moving wedge with heat and mass transfer. The effects of thermal diffusion and diffusion thermo with induced magnetic field are taken in consideration. The governing partial differential equations are transformed into nonlinear ordinary differential equations by applying the similarity transformation and solved numerically by using finite difference method (FDM). The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…El-Dabe et al reported the numerical treatment for casson fluid [11]. The effects of different parameters of self-similar nature was described in his study.…”
Section: Introductionmentioning
confidence: 97%
“…El-Dabe et al reported the numerical treatment for casson fluid [11]. The effects of different parameters of self-similar nature was described in his study.…”
Section: Introductionmentioning
confidence: 97%
“…Due to extensive practical applications of MHD in technological processes such as plasma studies, petroleum industries, MHD power generator designs, design for cooling of nuclear reactors, and construction of heat exchangers and on the performance of many other systems, there are many studies that considered MHD fluid flow past a wedge. These include the work of Abbasbandy et al [10] who examined the effects of MHD in the Falken-Skan flow of Maxwell fluid, and El-Dabe et al [11] considered the MHD boundary layer flow of non-Newtonian 2 Mathematical Problems in Engineering Casson fluid on a moving wedge with heat and mass transfer. Khan et al [12] also analyzed MHD laminar boundary layer flow past a wedge with the influence of thermal radiation, heat generation, and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Jamalabadi et al [13] analyzed the formulation of subcooled boiling flow of nanofluid under the effect of a magnetic field. El-Dabe et al [14] studied the characteristics of heat and mass transfer on MHD boundary layer flow of non-Newtonian fluid on a moving wedge. Khan et al [15] also found the numerical assets on MHD laminar boundary layer flow past a wedge with the effects of, heat generation, thermal radiation and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%